A default contagion model for pricing defaultable bonds from an information based perspective. Issue 1 (2nd January 2023) - Nakagawa, Hidetoshi; Takada, Hideyuki
Abstract : In this study, we introduce an extension of the information based model of credit risk proposed by Brody, Hughston and Macrina (2010) to a multi-name case to investigate how default contagion risk influences the price fluctuation of defaultable discount bonds. Under the model with a couple of obligors, we derive a stochastic differential equation for one defaultable zero-recovery discount bond price process to reflect default contagion risk of a counterpart debt obligor. As a consequence, we find that the excess rate of the return in the trend term of the bond consists of not only the issuer's hazard rate but also the counterpart obligor's hazard rate adjusted with the 'pseudo-default loss' rate. We also find that the bond price can jump at the default time of the counterpart by the amount dependent on the correlation between the issuer and the counterpart. Moreover, we numerically examine the impact of default contagion risk on some bond price components within the model.